Costs and consequences of treatment for mild gestational diabetes mellitus - evaluation from the ACHOIS randomised trial - Willson Kristyn J; Hiller Janet E; Crowther Caroline A; Moss John R; Robinson Jeffrey S (BMC, 2007)
Abstract Background Recommended best practice is that economic evaluation of health care interventions should be integral with randomised clinical trials. We performed a cost-consequence analysis of treating women with mild gestational diabetes mellitus by dietary advice, blood glucose monitoring and insulin therapy as needed compared with routine pregnancy care, using patient-level data from a multi-centre randomised clinical trial. Methods Women with a singleton pregnancy who had mild gestational diabetes diagnosed by an oral glucose-tolerance test between 24 and 34 weeks' gestation and their infants were included. Clinical outcomes and outpatient costs derived from all women and infants in the trial. Inpatient costs derived from women and infants attending the hospital contributing the largest number of enrolments (26.1%), and charges to women and their families derived from a subsample of participants from that hospital (in 2002 Australian dollars). Occasions of service and health outcomes were adjusted for maternal age, ethnicity and parity. Analysis of variance was used with bootstrapping to confirm results. Primary clinical outcomes were serious perinatal complications; admission to neonatal nursery; jaundice requiring phototherapy; induction of labour and caesarean delivery. Economic outcome measures were outpatient and inpatient costs, and charges to women and their families. Results For every 100 women with a singleton pregnancy and positive oral glucose tolerance test who were offered treatment for mild gestational diabetes mellitus in addition to routine obstetric care, $53,985 additional direct costs were incurred at the obstetric hospital, $6,521 additional charges were incurred by women and their families, 9.7 additional women experienced induction of labour, and 8.6 more babies were admitted to a neonatal nursery. However, 2.2 fewer babies experienced serious perinatal complication and 1.0 fewer babies experienced perinatal death. The incremental cost per additional serious perinatal complication prevented was $27,503, per perinatal death prevented was $60,506 and per discounted life-year gained was $2,988. Conclusion It is likely that the general public in high-income countries such as Australia would find reductions in perinatal mortality and in serious perinatal complications sufficient to justify additional health service and personal monetary charges. Over the whole lifespan, the incremental cost per extra life-year gained is highly favourable. Trial Registration Australian Clinical Trials Registry ACTRN12606000294550